2022
DOI: 10.7717/peerj.13992
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-carnitine supplementation for women with polycystic ovary syndrome: a systematic review and meta-analysis

Abstract: Background Polycystic ovary syndrome (PCOS) is a disorder in reproductive age women and is characterized by hyperandrogenic anovulation and oligo-amenorrhea, which leads to infertility. Anovulation in PCOS is associated with low follicle-stimulating hormone levels and the arrest of antral follicle development in the final stages of maturation. L-carnitine (LC) plays a role in fatty acid metabolism, which is found to be lacking in PCOS patients. This systematic review and meta-analysis aimed to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(157 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that carnitines improve ovulation, clinical pregnancy, insulin resistance, and body mass index (BMI) in infertile women with PCOS along with having positive effects on serum lipid profile. Nevertheless, low to moderate certainty of evidence about these effects is reported [ 15 , 16 , 17 ], thereby stimulating further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that carnitines improve ovulation, clinical pregnancy, insulin resistance, and body mass index (BMI) in infertile women with PCOS along with having positive effects on serum lipid profile. Nevertheless, low to moderate certainty of evidence about these effects is reported [ 15 , 16 , 17 ], thereby stimulating further investigation.…”
Section: Introductionmentioning
confidence: 99%